Luchando contra el olvido : el largo trayecto de las víctimas del metro de Valencia - Ballester, Laura; Évole, Jordi; Garrote, Beatriz (Barcelona : Editorial UOC, 2015)
About the accident that happened in Valencia's underground on July 3rd, 2006.
Online resource; title from PDF title page (Digitalia, viewed March 15, 2017)
Keywords: Railroad accidents -- Spain -- Valencia -- History; Salvados (Television program); Electronic books